A single breath of nitric oxide does not alter pulmonary perfusion pressure. Issue 12 (27th September 2022) - Brotto, Andrew R.; Beaudry, Rhys; Rowland, Samira; van Diepen, Sean; Stickland, Michael K.
Abstract : New Findings: What is the central question of this study? Is the amount of inhaled nitric oxide (NO) used during a diffusing capacity for inhaled NO manoeuvre sufficient to reduce pulmonary artery systolic pressure (PASP)? What is the main finding and its importance? These findings suggest that a single breath of inhaled NO does not change PASP, and combined with previous correlational work, further validates the use of the diffusing capacity for NO manoeuvre as a technique to determine pulmonary capillary blood volume and membrane diffusing capacity. Abstract: The measurement of diffusing capacity is an important pulmonary function test to evaluate gas exchange. Using both carbon monoxide and nitric oxide (NO), the diffusing capacity for nitric oxide ( D L, NO ) technique allows for the partitioning of capillary blood volume and membrane diffusing capacity. However, inhaled NO is known to dilate pulmonary arterioles in both health and disease and therefore could alter the outcomes that the D L, NO technique aims to quantify. The purpose of the study was to determine if a D L, NO manoeuvre alters pulmonary perfusion pressure. Nine participants completed 12 simulated 10‐s breath‐hold D L, NO manoeuvres ( n  = 6 placebo inhalations and n  = 6 with 40 ppm NO; order randomized) during which tricuspid regurgitant jet velocity was recorded continuously using Doppler ultrasound to estimate pulmonary artery systolic pressure (PASP) as a surrogate for pulmonary perfusion pressure. The PASP was not different between the placebo and NO conditions ( P  = 0.742). These data indicate that a single D L, NO manoeuvre does not alter PASP and therefore would not be expected to acutely alter pulmonary capillary blood volume or membrane diffusing capacity.